Care burden and related factors among informal caregivers of patients with amyotrophic lateral sclerosis - ÖZAYDIN, AYŞE NİLÜFER; CÖBEK ÜNALAN, GÜLRU PEMRA (My University, 2022)
Objective: Amyotrophic lateral sclerosis (ALS) affects the life of the family caregiver as well as the patient. This study aimed to determine the care burden and related factors among family caregivers of Turkish ALS patients. Methods: This descriptive study was conducted with 108 ALS patients and their informal caregivers through face-to-face interviews at home. The data were collected using the ALS Functional Rating Scale, Zarit Burden Interview, European Quality of Life-Five Dimensions Questionnaire, Multidimensional Scale of Perceived Social Support, and the Hospital Anxiety and Depression Scale. Results: The mean age of the caregivers was 48.1 ± 13.4 years; the vast majority were female, and they were either spouses or children of the patients. While 49.1% reported moderate or severe burden, the quality of life was moderate (mean 70.4 ± 22.8). The caregiver burden was related to sex and the functional state of the patient, as well as caregiver factors such as the relation to the patient, sex, health status, time spent for care, and living in the same house with a limited environment. Walking ability, percutaneous endoscopic gastrostomy, tracheostomy, and communication problems were not associated with the burden. Furthermore, burden was associated with the caregiver’s quality of life, social support, anxiety, and depression. Conclusions: The present study draws attention to the fact that the care burden in family caregivers of ALS patients is high and their quality of life is impaired. Our findings reveal that not only ALS patients but also caregivers need to be supported with an organized and planned system.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Amyotrophic lateral sclerosis; caregivers; quality of life; caregiver burden; psychosocial outcomes